2019
DOI: 10.3390/ijms20081994
|View full text |Cite
|
Sign up to set email alerts
|

RSK2-Mediated ELK3 Activation Enhances Cell Transformation and Breast Cancer Cell Growth by Regulation of c-fos Promoter Activity

Abstract: Ribosomal S6 kinase 2 (RSK2), regulated by Ras/Raf/MEKs/ERKs, transmits upstream activation signals to downstream substrates including kinases and transcription and epigenetic factors. We observed that ELK members, including ELK1, 3, and 4, highly interacted with RSK2. We further observed that the RSK2-ELK3 interaction was mediated by N-terminal kinase and linker domains of RSK2, and the D and C domains of ELK3, resulting in the phosphorylation of ELK3. Importantly, RSK2-mediated ELK3 enhanced c-fos promoter a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 52 publications
(74 reference statements)
3
23
0
Order By: Relevance
“…Our current study demonstrated that ELK3 acts as a positive regulator on PCa cell growth, migration, and EMT, and which knockdown results in cell migration inhibition may partly due to upregulation of SERPINE1 via the activation of AKT. ELK3 belongs to the ETS oncogene family and plays an important role in many biological processes such as cell proliferation, migration, invasion, and angiogenesis [11][12][13][14], which has been proved to promote the progression of several types of tumors including breast cancer, liver cancer, and squamous cell carcinomas [11-13, 15, 31]. On the contrary, some researchers reported that ELK3 was less expressed in cervical cancer and pancreatic cancer, and its ectopic expression inhibited the growth of these cancer cells [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our current study demonstrated that ELK3 acts as a positive regulator on PCa cell growth, migration, and EMT, and which knockdown results in cell migration inhibition may partly due to upregulation of SERPINE1 via the activation of AKT. ELK3 belongs to the ETS oncogene family and plays an important role in many biological processes such as cell proliferation, migration, invasion, and angiogenesis [11][12][13][14], which has been proved to promote the progression of several types of tumors including breast cancer, liver cancer, and squamous cell carcinomas [11-13, 15, 31]. On the contrary, some researchers reported that ELK3 was less expressed in cervical cancer and pancreatic cancer, and its ectopic expression inhibited the growth of these cancer cells [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Wasylyk et al identified a novel pyrazole XRP44X that inhibited fibroblast growth factor 2-induced ELK3 phosphorylation by the Ras-Erk signaling and led to G2-M cell cycle arrest in NIH3T3 fibroblasts and HUVEC endothelial cells [36]. Recently, Yoo et al reported that knockdown of ELK3 suppressed cell proliferation with accumulation at the G1 cell cycle phase in MDA-MB-231 breast cancer cells [11]. However, in contrast, ELK3 overexpression inhibited the cell cycle progression of pancreatic carcinoma cells, resulting in an increase in G0/G1 phase fraction and a decrease in S phase fraction [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under basic conditions, ELK3 is a transcriptional repressor, but it can be activated by RAS/ERK signals and mitogen-activated protein kinase (Mitogen-Activated Protein Kinase, MAPK) pathways to turn it into a transcription activator [ 28 , 29 ]. In recent years, ELK3 has been proven to play an important role in the occurrence and development of breast cancer, liver cancer, lung cancer, and other malignant tumors [ 30 33 ]. In prostate cancer studies, it has been shown that inhibition of ELK3 can promote cycle arrest and apoptosis of tumor cells [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…25 c-Fos has been shown to interfere with cell proliferation and induce cell transformation. 53,54 c-Jun is a member of Ap-1, as well as the most potent transcriptional activator of Ap-1. 55 c-Jun was shown to regulate cellular proliferation and apoptosis.…”
Section: Discussionmentioning
confidence: 99%